PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH PADA TEMA 6 CITA-CITAKU SUBTEMA 1 PEMBELAJARAN 1 UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI KELAS IV SD NEGERI DENDENG KABUPATEN KUPANG - Silvester P. Taneo; Netty E. A. Nawa; Derick I. Dima (Universitas Nusa Cendana, 2023)
This study aims to improve student learning outcomes in learning about theme 6 My Dreams, sub-theme 1 Me and My Dreams learning-1 with the Make a match learning model in grade 4 SD Negeri Dendeng. This type of research is Classroom Action Research. Which is an examination of learning activities in the form of actions, which are deliberately raised and occur in a class together, with the following stages: Planning, Implementation, Observation and Reflection. By taking the location at Dendeng Public Elementary School, Kupang Regency Class 4. The subjects of this research were 20 grade 4 students. Data collection was carried out by observation and test techniques. The results of observations of teacher activity in the first cycle, the class average value was 64.28 and in the second cycle, the second cycle average value was 80.35. Then observation of student activity in cycle I obtained class success of 55.7% and in cycle II obtained 76.8%. Meanwhile, the percentage of learning completeness in cycle I was 35% in cycle II, with an increase in percentage of 100%. Make a match in learning about theme 6 My Dreams Sub-theme 1 Me and My Dreams in the 1st lesson can improve student learning outcomes in grade 4 SD Negeri Dendeng, Kupang Regency.